The use of ruxolitinib for acute graft‐versus‐host disease developing after solid organ transplantation. Issue 2 (11th September 2019) - Jacobs, Miriam T.; Olson, Marissa; Ferreira, Bruna Pellini; Jin, Ramon; Hachem, Ramsey; Byers, Derek; Witt, Chad; Ghobadi, Armin; DiPersio, John F.; Pusic, Iskra
Abstract : Development of graft‐versus‐host disease (GvHD) is a rare complication after transfusions or solid organ transplantation. Patients typically present with a skin rash, diarrhea, liver failure, and bone marrow aplasia. A diagnosis of transfusion/transplantation associated‐GvHD is made based on the clinical and histologic evidence, yet it is often delayed due to the nonspecific symptoms attributed to the patient's underlying illness. Several therapeutic approaches are being used including both increasing and withdrawing immunosuppression, and the use of cellular therapies. Unfortunately, the success rate of these approaches is low and the mortality of this complication is very high. New approaches are needed. We report on three cases of GvHD developing after solid organ transplantation treated with ruxolitinib. Abstract : The authors report on three cases of graft‐versus‐host disease that developed after solid organ transplantation and were treated with ruxolitinib.